Impact of the Oncology Care Model on End‐of‐Life Care. (15th September 2021) - Zheng, Qing; Christian, Thomas; McClellan, Sean; Glass, Roberta; Keating, Nancy; Brooks, Gabriel; Hassol, Andrea
Abstract : Research Objective: The Oncology Care Model (OCM) is a six‐year episode‐based alternative payment model for cancer care launched by the Centers for Medicare & Medicaid Services in July 2016. OCM includes several elements intended to improve end‐of‐life (EOL) care. We evaluated the impact of OCM on EOL care intensity, spending, and oncologist and patient experiences. Study Design: Using 100% Medicare claims (2014–2019) we employed a Difference‐in‐Differences (DID) approach comparing changes over time in care intensity and Medicare payments at the end of life, for beneficiaries served by OCM practices and by a propensity‐score matched comparison group of non‐participating practices. We also surveyed caregivers of deceased beneficiaries about patient experiences in the last month of life, and we surveyed oncologists from OCM practices about changes in palliative and EOL care. Finally, we conducted case studies with over 40 OCM practices. Population Studied: Claims‐based analyses included 256, 102 Medicare beneficiaries in OCM or comparison practices who underwent chemotherapy for cancer and died during or within 90 days of their last OCM‐defined episode. Surveys were completed by family members of 5786 deceased beneficiaries (55% OCM, 45% comparison) and by 400 oncologists working in OCM practices. Principal Findings: OCM led to fewer hospitalization in the last 30 days of life for deceased OCM versus comparison beneficiaries (DID:‐11 per 1000 beneficiaries (90%CI:‐19, −4). OCM had no impact on outpatient emergency department use in the last month of life, use of infused chemotherapy in the last two weeks of life, or on hospice use, duration, or timing. The average Medicare Part A payments during the last episode for deceased beneficiaries rose $440 less in the OCM group than in comparisons, a 2.4 percent relative reduction from the OCM baseline mean of $18, 530 (p ≤ 0.05). OCM had no impact on average total episode payments, or on Medicare Part B or D payments, during deceased beneficiaries' last episodes. OCM did not affect caregivers' perceptions: survey respondents rated EOL care highly before OCM began, and there were no changes over time and no differences between OCM and comparison respondents. Roughly one third of oncologists reported enhancing access to palliative care (36%) and using new/enhanced standards or guidelines to trigger discussions about EOL goals and hospice (32%). Most oncologists (55%) reported that OCM improves quality of EOL care. Conclusions: OCM led to a small relative reduction in hospitalizations during deceased beneficiaries' last month of life and a corresponding relative decrease in Medicare Part A payments. OCM had no impact on hospice use, duration, or timing. OCM had no impact on beneficiaries' care experiences at the end of life. Oncologists reported EOL process improvements attributable to OCM. Implications for Policy or Practice: OCM emphasizes shared decision making and advance care planning to ensure that cancer beneficiaries' EOL wishes are documented and followed. The first three years of OCM suggest that these efforts led to small relative reductions in hospitalizations and Part A payments in the last month of life. The lack of impact on hospice use/timing, despite clinician‐reported EOL care process improvements, suggests ongoing areas for potential improvements. Primary Funding Source: Centers for Medicare and Medicaid Services.